(untitled) (Journal of the College of Languages (JCL), 2025)
Linguistic researches on stylistic or ideological investigation of political speeches are in high but separate volumes leaving a gap in stylo-ideological analysis. This paper investigated style and ideology in No Enemies to Fight: Goodluck Jonathan on the Mable, a compendium of quotable quotes from the former Nigerian President Goodluck Jonathan’s speeches. Reading through, prominent linguistic features that project the writer’s ideologies were identified, and then analyzed quantitatively and qualitatively, employing the theoretical framework of Halliday’s Systemic Functional Linguistics. Jonathan deployed simple syntactic structures, inclusive person deixes and lexical reiterations to advance personal and political ideologies founded on honesty, humility, fairness, forgiveness, friendship, openess, prudence and respect for the rule of law.These held beliefs earned him the desired public acceptance and support. The research has not only unraveled Jonathan’s ideologies; it has also thrown lights on the deployment of stylistics for espousing ideological positions in political speeches.